Higher cardiovascular risks and Atherogenic Index of Plasma found in police officers of developing country in Surabaya, East Java, Indonesia - Meity Ardiana; Primasitha Maharany Harsoyo; Hanestya Oky Hermawan; Inna Maya Sufiyah; Dwika Rasyid Firmanda; Saskia Ratna Desita; Annisya Dinda Paramitha; Arisvia Sukma Hariftyani; Farah Aisha Shabrina; Fita Triastuti (Elsevier, 2022)
Background: Police officers are known for fieldwork shifts, psychological stress, and prolonged physical activity that are associated with cardiovascular disease (CVD). We aim to determine the differences in CVD risks factor and Atherogenic Index of Plasma (AIP) profiles as a predictor of cardiac events between police officers and civilians in a developing country as an evaluation and strategic preventive measure for CVD. Methods: 978 participants were enrolled as subjects in this cross-sectional study. Data used were obtained during medical check-ups using complete physical and laboratory examinations including blood pressure, body mass index (BMI), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol, fasting blood sugar, and AIP between 2019 and 2020 at Bhayangkara State Police Hospital Surabaya. Mann-Whitney U test was performed using IBM SPSS version 25. Results: There are significant differences in systolic (p = 0.000) and diastolic blood pressure (p = 0.003), triglycerides (p = 0.000), LDL-C (p = 0.006), total cholesterol (p = 0.000), fasting blood glucose (p = 0.001), and the AIP (p = 0.000) between the police and civilian groups, with the latter showing a tendency of having higher rates. Conclusions: CVD risk was found in both groups. Nevertheless, police officers have higher AIP and overall CVD risk compared to civilians, creating a necessity for aggressive CVD prevention strategies within the population.